2006
DOI: 10.1177/002204260603600402
|View full text |Cite
|
Sign up to set email alerts
|

Initiation to Pharmaceutical Opioids and Patterns of Misuse: Preliminary Qualitative Findings Obtained by the Ohio Substance Abuse Monitoring Network

Abstract: Pharmaceutical opioid misuse has been recognized as a growing public health problem across the nation. To develop appropriate treatment and prevention programs, the population of pharmaceutical opioid abusers has to be well understood. This exploratory study is based on qualitative interviews with 24 people in the Dayton/Columbus, Ohio, area. Interviews were conducted for the Ohio Substance Abuse Monitoring Network, a statewide epidemiological surveillance system. Participants ranged in age from 18 to 48 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 29 publications
4
56
0
Order By: Relevance
“…Our findings complement other literature citing social settings as the most common contexts for initiation to non-medical prescription drug use [16], and PO initiation specifically [5,18,21]. Interestingly, our data contained a higher proportion of non-oral initiates that those reported in other prior studies of young adult PO misusers [5,18], suggesting that the use of alternate routes may be more prevalent than previously reported.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings complement other literature citing social settings as the most common contexts for initiation to non-medical prescription drug use [16], and PO initiation specifically [5,18,21]. Interestingly, our data contained a higher proportion of non-oral initiates that those reported in other prior studies of young adult PO misusers [5,18], suggesting that the use of alternate routes may be more prevalent than previously reported.…”
Section: Discussionsupporting
confidence: 87%
“…Motivations for illicit prescription drug use among young adults [16] and high school student PO misusers [19] have been examined, as well as the onset of PO abuse among drug treatment clients [20] and other populations of substance abusers [21]. Other literature has also documented PO opioid initiation sources among youth and young adult populations of injection drug users [5] however, few studies have explored how social context may influence initiation to PO misuse via alternate routes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the qualitative interview allowed the researcher to ask follow up questions and seek clarification. This research method has been used to study a variety of sensitive topics including marijuana and other drug usage (Hallstone 2006), marijuana cultivation (Hammersvik, Sandberg and Pedersen 2012;Riggs, Hafley and Tewksbury 1996;Weisheit 1990),methamphetamine usage (Daniulaityte, Carlson and Kenne2007), pharmaceutical opioid abuse (Daniulaityte, Carlson and Kenne 2006), human sex trafficking (Troshynski and Blank 2008) and alcohol consumption among young American adults (Antin, Paschall and Nygaard 2010) and citizens of India (Gaunekar, et al 2004). Additionally, previous research on moonshining has used the qualitative interview method (Peine and Schaft 2012;Wigginton 1971).…”
Section: Methodsmentioning
confidence: 99%
“…Research during the last decade has established that individuals who abuse prescription opioids, especially those with a physiological dependence, may shift to heroin use, particularly when they already inhale or inject prescription opioids [6][7][8][9][10][11][12][13][14][15][16][17]. Several of these studies have found remarkably high likelihoods of heroin abuse after NMPO than without NMPO, as high as 19 times using data from 2011 [12], to nearly 40 times using data from 2013 [18].…”
Section: Introductionmentioning
confidence: 99%